COVID-19 vaccine equity and the right to health for displaced Venezuelans in Latin America. - David C Hill; Zafiro Andrade-Romo; Karla Solari; Ellithia Adams; Lisa Forman; Daniel Grace; Alfonso Silva-Santisteban; Amaya Perez-Brumer (PLOS Global Public Health, 2023)
Given the magnitude of Venezuelan displacement in Latin America, there is a need to assess how migrants were, and will continue to be, addressed in COVID-19 vaccination policies. To explore migration status as a dimension of vaccine equity in Latin America and in relation to international human rights, we assessed national vaccination plans, peer-reviewed, and gray literature published between January 2020 and June 2021. Three key rights-related concerns were found to restrict the health rights of migrants in the region: 1) lack of prioritization of migrants in vaccine distribution; 2) onerous documentation requirements to be eligible for COVID-19 vaccination; and (3) how pervasive anti-migrant discrimination limited equitable health care access. While international human rights law prohibits against discrimination based on migration status, few countries analyzed realized their obligations to provide equal access to COVID-19 vaccines to non-citizens, including displaced Venezuelans. Especially for migrants and displaced people, effective and sustainable vaccination strategies for COVID-19 and future pandemics in Latin America must be guided not only by epidemiological risk but also seek to align with human rights obligations. To achieve this, States must also take special measures to facilitate vaccine access for communities facing systemic discrimination, exclusion, and marginalization.